2006
DOI: 10.1080/08927010500499563
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence elastomeric coating performance: the effect of coating thickness on basal plate morphology, growth and critical removal stress of the barnacleBalanus amphitrite

Abstract: Silicone coatings are currently the most effective non-toxic fouling release surfaces. Understanding the mechanisms that contribute to the performance of silicone coatings is necessary to further improve their design. The objective of this study was to examine the effect of coating thickness on basal plate morphology, growth, and critical removal stress of the barnacle Balanus amphitrite. Barnacles were grown on silicone coatings of three thicknesses (0.2, 0.5 and 2 mm). Atypical (''cupped'') basal plate morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 24 publications
(31 reference statements)
6
89
0
Order By: Relevance
“…As for the zoospores of algae, antifouling tests targeting barnacles frequently focus on the sessile stage, which are cyprids that hatched from the adult organisms [91][92][93]. The two conventional approaches to study the interaction of these microorganisms with a surface involve settlement assays of competent larvae [97] and/or the mechanical removal of adults organisms in order to estimate the adhesion strength [42,44,94,95]. A simplified life-cycle of barnacles (Fig.…”
Section: Barnacle Cyprids: Motile and Selective Larvae As Early Stagementioning
confidence: 99%
“…As for the zoospores of algae, antifouling tests targeting barnacles frequently focus on the sessile stage, which are cyprids that hatched from the adult organisms [91][92][93]. The two conventional approaches to study the interaction of these microorganisms with a surface involve settlement assays of competent larvae [97] and/or the mechanical removal of adults organisms in order to estimate the adhesion strength [42,44,94,95]. A simplified life-cycle of barnacles (Fig.…”
Section: Barnacle Cyprids: Motile and Selective Larvae As Early Stagementioning
confidence: 99%
“…Such factors include surface energy (Brady and Singer 2000;Anderson et al 2003), coating wettability (Dahlstrom et al 2004), modulus and thickness Wendt et al 2006), fracture mechanics and materials used (Burnell et al 1998;.…”
Section: Foul-release Coatings At Workmentioning
confidence: 99%
“…(Darwin 1851) Figure 4. Barnacle cement production diagram (Khandeparker and Anil 2007) Though not much is know about the composition of cement, many studies have successfully identified changes in barnacle removal stress from various surfaces (Berglin and Gatenholm 1999;Swain et al 2000;Berglin et al 2001;Sun et al 2004;Wendt et al 2006). The study conducted by Sun et al (2004) shows that the cement, which forms below the basal plate, is a multilayered structure of adhesive plaque.…”
Section: Barnacles In a Dynamic Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common method to minimise biofouling is to coat the submerged surface with an antifouling (AF) paint that leaches biocide(s) to prevent marine life from attaching to the surface (Yebra et al 2004). A number of alternative technologies are available commercially, the most notable being based on silicone elastomers, which release accumulated fouling under suitable hydrodynamic conditions (eg Kavanagh et al 2005;Wendt et al 2006).…”
Section: Introductionmentioning
confidence: 99%